Screening NLRP3 drug candidates in clinical development: lessons from existing and emerging technologies - Tengesdal, Isak W.; Banks, Migachelle; Dinarello, Charles A.; Marchetti, Carlo (Frontiers in Immunology, 2024)
Decades of evidence positioned IL-1β as a master regulatory cytokine in acute and chronic inflammatory diseases. Approved biologics aimed at inhibiting IL-1 signalling have shown efficacy but variable safety. More recently, targeting NLRP3 activation, an upstream mediator of IL-1β, has garnered the most attention. Aberrant NLRP3 activation has been demonstrated to participate in the progression of several pathological conditions from neurogenerative diseases to cardio-metabolic syndromes and cancer. Pharmacological and genetic strategies aimed to limit NLRP3 function have proven effective in many preclinical models of diseases. These evidences have lead to a significant effort in the generation and clinical testing of small orally active molecules that can target NLRP3. In this report, we discuss different properties of these molecules with translational potential and describe the technologies currently available to screen NLRP3 targeting molecules highlighting advantages and limitations of each method.